University students’ perception of Online Distance Learning (ODL) mode during Covid-19 pandemic / Aminabibi Saidalvi … [et al.] - Saidalvi, Aminabibi; Noorezam, Maisarah; Zakaria, Nursyuhada; Sa’adan, Nadzrah; Rasdi, Nurul Nadiah (Akademi Pengajian Bahasa, 2021)
The Covid-19 pandemic and the subsequent Movement Control Order (MCO) imposed by the Malaysian government has resulted in all formal classroom learning for around 4.9 million students at all levels of education nationwide was suspended since mid-March 2020. Educators were advised to find the best alternatives to deliver lessons, resulting in a shift from traditional classroom meetings to distance learning online or offline. However, the reality is, the majority of the students are still grappling with e-learning, inadequate equipment, and an unconducive environment making the adoption of home-based e-learning even harder. This thus suggests that there is no evidence on how Diploma students are experiencing this new normal. Having realised the importance of getting first-hand information regarding online distance learning (ODL) experiences, this study investigated university students’ experiences of ODL mode amidst COVID-19. An online survey using Google Forms through Whatsapp and e-mail was utilised in this study for three weeks as a mode of collecting data from 486 students from all diploma courses in a university in the southern region of Peninsular Malaysia. Using descriptive quantitative and qualitative analysis, the distribution of study participants, learning experiences, and expectations on educational decisions of ODL was investigated. As classes move online in the foreseeable future, the findings of this project will benefit UiTM and the government in planning and restructuring digital education post-Covid-19 to develop employability and the productivity of the future generation.